2018
DOI: 10.1002/jrs.5390
|View full text |Cite
|
Sign up to set email alerts
|

SILAR grown Ag nanoparticles as an efficient large area SERS substrate

Abstract: Ag nanoparticles having different size and coverage are grown on large area glass substrate (~10 cm2) using low cost successive ionic layer adsorption and reduction (SILAR) method. The SILAR parameters, such as reduction time and growth cycles are optimized to grow Ag nanoparticles with appropriate size and coverage showing maximum surface enhanced Raman scattering (SERS) enhancement of Rhodamine 6 G(R6G). For fixed growth cycles, the size and the coverage of the grown Ag nanoparticles are found to increase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Therefore the rest contribution (~ 10 2 ) is most probably from the CE mechanism which is confirmed by the observed shift in the peak position and presence of 247 cm -1 Raman peak of AgNPs@Clsurface complex in MB SERS spectra [53]. It is quite difficult to compare the obtained GSERS value with the available literature due to the fact that different MB concentrations, laser sources with different powers were used in the literature to calculate the GSERS values [16,43,54]. However it is noteworthy with low laser power (60 μW), the AgT1k SERS substrate shows excellent sensitivity (10 -10 M) and SERS enhancement (GSERS ~ 3.2×10 9 ) factor as compared with the literature.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore the rest contribution (~ 10 2 ) is most probably from the CE mechanism which is confirmed by the observed shift in the peak position and presence of 247 cm -1 Raman peak of AgNPs@Clsurface complex in MB SERS spectra [53]. It is quite difficult to compare the obtained GSERS value with the available literature due to the fact that different MB concentrations, laser sources with different powers were used in the literature to calculate the GSERS values [16,43,54]. However it is noteworthy with low laser power (60 μW), the AgT1k SERS substrate shows excellent sensitivity (10 -10 M) and SERS enhancement (GSERS ~ 3.2×10 9 ) factor as compared with the literature.…”
Section: Resultsmentioning
confidence: 91%
“…AgT1k SERS substrate. SERS enhancement factor (GSERS) equation (see supplementary information) can be written as below [16,52],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaikh et al have grown AgNPs having different size and coverage on a large area glass substrate using the low‐cost successive ionic layer adsorption and reduction method. They report that measured relative standard deviation values of AgNPs grown with optimum successive ionic layer adsorption and reduction parameters suggest an excellent homogeneity and reproducibility of the SERS signal . Stolcova and co‐workers described gold films over very small (107 nm) spheres as an efficient substrate for sensitive and reproducible SERS detection of biologically important molecules .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…They report that measured relative standard deviation values of AgNPs grown with optimum successive ionic layer adsorption and reduction parameters suggest an excellent homogeneity and reproducibility of the SERS signal. [20] Stolcova and co-workers described gold films over very small (107 nm) spheres as an efficient substrate for sensitive and reproducible SERS detection of biologically important molecules. [21] Wu et al reported both solution and solid substrates with built-in calibration for quantitative SERS applications.…”
Section: Sers Substratesmentioning
confidence: 99%